The Wnt/β-Catenin Pathway Regulated Cytokines for Pathological Neuropathic Pain in Chronic Compression of Dorsal Root Ganglion Model - Zhang, Ye; Zhao, Dan; Li, Xutong; Gao, Beiyao; Sun, Chengcheng; Zhou, Shaoting; Ma, Yanhong; Chen, Xuemei; Xu, Dongsheng (Journal of neural transplantation & plasticity, 2021)
Neuropathic pain is one of the important challenges in the clinic. Although a lot of research has been done on neuropathic pain (NP), the molecular mechanism is still elusive. We aimed to investigate whether the Wnt/β-catenin pathway was involved in NP caused by sustaining dorsal root ganglion (DRG) compression with the chronic compression of dorsal root ganglion model (CCD). Our RNA sequencing results showed that several genes related to the Wnt pathway have changed in DRG and spinal cord dorsal horn (SCDH) after CCD surgery. Therefore, we detected the activation of the Wnt/β-catenin pathway in DRG and SCDH and found active β-catenin significantly upregulated in DRG and SCDH 1 day after CCD surgery and peaked on days 7-14. Immunofluorescence results also confirmed nuclear translocalization of active β-catenin in DRG and SCDH. Additionally, rats had obvious mechanical induced pain after CCD surgery and the pain was significantly alleviated after the application of the Wnt/β-catenin pathway inhibitor XAV939. Furthermore, we found that the levels of proinflammatory factors tumor necrosis factor-α (TNF-α) and interleukin-18 (IL-18) were significantly elevated in CCD rat serum, while the levels of them were correspondingly decreased after the Wnt/β-catenin pathway being inhibited. The results of Spearman correlation coefficient analysis showed that the levels of TNF-α and IL-18 were negatively correlated with the mechanical withdrawal thresholds (MWT) after CCD surgery. Collectively, our findings suggest that the Wnt/β-catenin pathway plays a critical role in the pathogenesis of NP and may be an effective target for the treatment of NP.